THE ANALYSIS OF CORPORATE SOCIAL RESPONSIBILITY IMPLEMENTATION BASED ON TRI HITA KARANA CONCEPT (A Case Study at the Meliá Bali Hotel) - I PUTU KHRISNAYUDI WIDIA (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2016)
This research is descriptive qualitative research that aims to identify and understand the implementation of CSR based on Tri Hita Karana at the Meliá Bali Hotel. The case study is used as a method of research and designed to answer the research questions. Thematic analysis is used to interpret the data. Furthermore, the data collection method are interview, observation and documentation. The result in this study reveals that first, CSR at Meliá Bali using the concept of Tri Hita Karana is Parahyangan, Pawongan and Palemahan, in which each aspect is done within the scope of internal (within the company) and external (outside the company). Second, the entire CSR activities are summarized in a special CSR report every month, which reported to Meliá Hotels International (MHI). It is because MHI has a policy that requires each of his hotel to carry out at least 5 social activities each month. Meliá Bali CSR report is separate from their financial statements and were made without following any guidelines. Third, Meliá Bali does not implement the budget-policy in implementing CSR. With huge funds obtained from various sources, any person who is deserving to be helped by them will be helped. Fourth, there are no significant problems faced by Meliá Bali in the implementation of their CSR. The only problems that often occurred was the lack of time to carry out CSR activities, due to the number of jobs in the hotel that need to be completed.Key words: Corporate Social Responsibility, Tri Hita Karana Concept, CSR Implementation, Meliá Bali Hotel